2022
DOI: 10.1186/s12877-022-03155-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of triglyceride glucose index with all-cause and cause-specific mortality among middle age and elderly US population

Abstract: Aims To investigate the association between the triglyceride glucose (TyG) index and all-cause and cause-specific mortality in middle age and elderly population. Methods and results A total of 9,254 participants with age ≥ 45 years were enrolled from the National Health and Nutrition Examination Survey cycle of 1999–2014. The TyG index was determined as ln [fasting triglycerides (mg/dL) x fasting glucose (mg/dL)/2]. Primary outcomes were all-cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…Numerous publications indicate that there is a nonlinear relationship between TyG index and cardiovascular mortality 32 . Meanwhile, among the middle‐aged and elderly US population in the National Health and Nutrition Examination Survey (NHANES), the second quartile of the TyG index encompasses the lowest risk of cardiovascular mortality (hazard ratio 0.62; 95% CI, 0.43‐0.88) when compared with the first quartile 33 . Lower TyG index also demonstrates higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous publications indicate that there is a nonlinear relationship between TyG index and cardiovascular mortality 32 . Meanwhile, among the middle‐aged and elderly US population in the National Health and Nutrition Examination Survey (NHANES), the second quartile of the TyG index encompasses the lowest risk of cardiovascular mortality (hazard ratio 0.62; 95% CI, 0.43‐0.88) when compared with the first quartile 33 . Lower TyG index also demonstrates higher risk.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study with more than 10 years of follow-up has found that the TyG index (as a surrogate for IR) was a significant risk factor for incident CVD/CHD with an issue that was more prominent among the younger population [33]. Moreover, the findings of Sun et al [34] showed that TyG index was associated with all-cause mortality and cause-specific mortality (CVD and malignant neoplasms) among middle age and elderly US population. These data support the utility of the TyG index as a reliable and valid marker of IR for risk stratification in the real world.…”
Section: Related Studiesmentioning
confidence: 99%
“…The TyG index has been reported to be a composite biochemical indicator that reflects the combined effect of glucose and lipids [ 20 ]. The relationship between DR and abnormal glycolipid metabolism indicators has been extensively discussed [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%